Analisis Kandungan Tepung Pati Labu Siam sebagai Alternatif Pengganti Tepung Tapioka dalam Pembuatan Olahan Kue/Camilan - Rofita, Dewi; Wahyu, Yuliana; Purnami, Wahyuni; Angkur, Maria F. M. (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Rofita, D., Wahyu, Y., Purnami, W., & Angkur, M. F. M. (2024). Analysis of chayote starch content as an alternative substitute for tapioca flour in making cakes/snacks. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 817–822). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The chayote plant (Sechium edule (Jacq.) Sw.) is a plant that is very easy to find in everyday life. Utilizing chayote essence as an alternative to tapioca flour can increase its useful value. The aimed of this research is to determine the nutritional content of chayote starch and to determine the organoleptic test for making snacks from chayote starch as an alternative to tapioca flour. This research was carried out in 2 stages, namely: 1) carrying out laboratory tests to analyze the nutritional content (carbohydrate, calorie, protein, fat and fiber content) of chayote starch flour, and 2) carrying out organoleptic tests of snacks made from chayote starch as raw material in an effort to looking for alternatives to tapioca flour. Organoleptic tests were given to 10 randomly selected panelists. The results of this research are: 1) the carbohydrate content of chayote starch is 6%, calories are 26 calories, protein is 0.6 grams, fat is 0.1%, and fiber is 2.2 grams. 2) organoleptic tests stated that on average the panelists liked snacks made from chayote starch in terms of color, aroma, taste, texture and appearance.